La función simbólica en el desarrollo del lenguaje en los niños de educación inicial ii de la unidad educativa Angel Polibio Chaves, ciudad de Guaranda, provincia de Bolívar, período 2018-2019. - Maldonado Silva, Gabriela Patricia (2019)
The objective of the present investigation is to determine the influence of the symbolic function in the development of language in the children of Initial II of the Educational Unit "Ángel Polibio Chaves", of the Guaranda canton, province of Bolívar. The methodology used is given under a qualitative approach, accompanied by a bibliographical research that helped to sustain theoretically the variables object of study from the criterion of different authors, also within the field research the PLON questionnaire was applied -R to the population structured by 25 children aged between 4 and 5 years in two moments; the first moment in the natural state; that is, without the need to apply any didactic tool as main findings it was possible to determine shortcomings in the development of the language in the majority of students of initial education II and the second moment of application was subsequent to the application of the proposed guide, where the results were evidently positive. Likewise, it was possible to verify the hypothesis raised through the Wilcoxon statistic since the obtained P value (0,005) is lower than 0,05, so the null hypothesis is rejected and the alternative hypothesis is accepted; that is to say that, The symbolic function SI improves the development the language in the children in initial II of the Educational Unit "Ángel Polibio Chaves" of the Guaranda canton. Keywords: PLON-R questionnaire, language development, initial education, symbolic function.